Luminous Effects in the Interior of the Church of St. Nikola The Wet in Yaroslavl’ and the Church the Resurrection in the Town of Romanov-Borisoglebsk - Rozhniatovskii, Vsevolod M. (Actual Problems of Theory and History of Art, 2015)
This study is aimed at the possible symbolic meaning of various luminous effects, which were recently observed in the Church of St. Nikola The Wet in Yaroslavl and the Church the Resurrection in the town of RomanovBorisoglebsk near Yaroslavl’. Several luminous combinations, which could be perceived as visual images in the semantic context of symbolic decorations, were recorded during this observation. The author comes to the conclusion that in order to create such an effect, an artist had to apply some special technics, bring his composition in correlation with the church structure and keep in mind during his work daily and seasonal changes in natural illumination inside the church. Luminous effects were an integral symbolic part of the interior décor of Byzantine and Old Russian churches. The article also deals with numerous historical documents that contain different evidence of an ongoing interest for light and fire symbolism in the 18th-century Russia.